Literasi Warga Desa Purwajaya, Terhadap Temuan dan Pemanfaatan Fosil Kayu - Nani Husien; Erwin; Agus Sulistyo Budi; Edy Budiarso; Zainul Arifin; Sujiman Kasnadi (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2022)
This activity intends to educate residents of Purwajaya Village with information, education, and awareness about the value of finding wood fossils in their area, and also provide input on the uses that can be made by the local residents who live near wood fossil finds. The discovery of the world's longest fossil wood log in Purwajaya Village, as well as in several other villages, attracts precious stone hunters and dealers who wish to dig up these historical natural resources assets to trade. If this trend continues, Borneo's botanical diversity would eventually decline. Most of the people are unaware of the hidden assets found in their village, namely fossil wood, and they are uninformed of the rewards they will receive if these assets are properly handled. The program took place in residential areas close to where the wood fossils were discovered, and it was entirely interactive. The activity stages include the presentation of wood fossils and continued discussions with residents. The results of the activity showed that the community's curiosity is very high, especially the people of Purwajaya Village towards the wood fossils found in their village, their history and its use. The activity went well, especially for the villagers as the participants from the Marga Mulya hamlet farmer group, Purwajaya Village. This can be seen from the discussion and the desire for similar activities to be carried out in the form of the practice of how to utilize fossil wood in the future.